Computational fluid dynamics study of magnetic liquid rotary seal for sealing liquid. (November 2020) - Wang, Hujun
Abstract: When applied in sealing liquid, the instability of the interface between the magnetic liquid and the sealed liquid in the direct-contact magnetic liquid seal structure will occur and increase, eventually leading to the failure of the magnetic liquid seal. In order to understand the destruction process of the interface between the magnetic liquid and the sealed liquid more intuitively, the two-phase flow of the magnetic liquid and the sealed liquid was simulated numerically. Phase distribution and velocity distribution are obtained through the simulation.